The Impact of The Online Learning Media "Blooket" on Senior High School Students' Reading Comprehension - Faticha Alvina Maharani Maharani (Retain: Journal of Research in English Language Teaching, 2025)
This research investigates the influence of Blooket, a game-based digital learning tool, on high school students' ability to comprehend narrative texts. A quantitative approach was adopted using a quasi- experimental design involving two distinct groups: the experimental group, which utilized Blooket, and the control group, which followed conventional instruction. A total of 68 eleventh-grade students from SMAS Kartika IV-3 Surabaya participated. Data collection was carried out through pre-tests and post-tests, focusing on five core components of reading comprehension: identifying the main idea, understanding vocabulary, making inferences, locating specific information, and recognizing reference words. The analysis revealed a statistically significant improvement in the experimental group compared to the control group (Sig. < .001), though the practical impact, as indicated by Cohen’s d (0.125), was relatively small. Among the measured aspects, notable progress was observed in identifying main ideas and reference words. These results suggest that Blooket can be an engaging educational resource that supports students’ reading comprehension, particularly when integrated with effective lesson planning.